THE REALIZATION OF THE INTENTIONAL ORIENTATION OF A.P. CHEKHOV'S PIECES IN P. BRUCK'S THEATRICAL DISCOURSE - Viktoriya Sychina; Vyacheslav Khodus (Гуманитарные и юридические исследования)
The study of the features of the director's realization of the intentional orientation of Chekhov's play "The Cherry Orchard" in P. Brook's theatrical text is based on auto-descriptive data obtained as a result of discourse interpretation of P. Brook's contemporaries. An auto-descriptive (or metapoetic) text is a text that includes the author's reflection on his own creative activity, as well as on any other texts of his associates. The research of some linguistic means shows how a descriptive text of a specific author's discourse is organized and what the most valuable key words of the determined text fragment are. The paper analyzes obscure facts, objectifies some criteria for identifying discursive words and determining their number. The subjective evaluation of the text gives grounds for key words searching: their choice is made on the basis of the author's dramatic intention, creative intent, communicative strategy of textual deployment, realized initially in the creative mind of the director, and then in the theatrical text. This is a kind of reconstruction of the verbal world and it looks like if the text of the play-score is the basis of the play-production, which forms a special director's discursive plan recreated from verbal instructions.